2007
DOI: 10.1128/jvi.01620-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1: Resistance to Nucleoside Analogues and Replicative Capacity in Primary Human Macrophages

Abstract: Antiretroviral treatment failure is associated with the emergence of resistant human immunodeficiency virus type 1 (HIV-1) populations which often express altered replicative capacity (RC). The resistance and RC of clinical HIV-1 strains, however, are generally assayed using activated peripheral blood mononuclear cells (PBMC) or tumor cell lines. Because of their high proliferation rate and concurrent high deoxynucleoside triphosphate (dNTP) content, both resistance and RC alterations might be misestimated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 67 publications
5
21
0
Order By: Relevance
“…2B showing that M184I RT displays only 50% of Met-184 Clone 3 RT at 0.25 M dNTP. More interestingly, it was reported that, unlike M184I virus, M184V virus is able to infect macrophages (30,31), and this observation is consistent with our biochemical data illustrated in Fig. 2A that M184V RT still maintains RT activity at least 50% of the wildtype RT activity even at low dNTP concentrations found in macrophages.…”
Section: Cellular Dntp Concentration-dependent Infectivity Of Hiv-1supporting
confidence: 81%
“…2B showing that M184I RT displays only 50% of Met-184 Clone 3 RT at 0.25 M dNTP. More interestingly, it was reported that, unlike M184I virus, M184V virus is able to infect macrophages (30,31), and this observation is consistent with our biochemical data illustrated in Fig. 2A that M184V RT still maintains RT activity at least 50% of the wildtype RT activity even at low dNTP concentrations found in macrophages.…”
Section: Cellular Dntp Concentration-dependent Infectivity Of Hiv-1supporting
confidence: 81%
“…Similar findings were also obtained using whole isolates obtained from patients failing tenofovir therapy (175). One study using single-cycle parallel cultures found a decreased fitness of K65R in primary macrophages but not in a cell line or primary human PBMCs (129). The replication defect of K65R correlates with a decrease in processivity of polymerization and in the polymerization rate, k pol , of purified reverse transcriptase (46,179).…”
Section: Mutations Conferring Resistance To Reversesupporting
confidence: 63%
“…M184V occurs frequently in viral isolates from patients failing lamivudine or emtricitabine therapy (63,153). M184V has a fitness similar to that of the wild type in most T-cell lines where nucleotide concentrations are high (10) but reduced fitness in primary cells that have limited nucleotide pools, such as PBMCs and macrophages (3,10,129). Of note is that there are some more-recent studies that have found reduced fitness of this mutant in cell lines (35,48).…”
Section: Mutations Conferring Resistance To Reversementioning
confidence: 99%
See 1 more Smart Citation
“…In HIV-1, the mutations K65R, Q151M, and M184V were found to result in replication defects. Mutation K65R reduces the replication capacity of HIV-1 in T-cell lines and monocytes (41,42), whereas mutation M184V results in reduced fitness in monocytes (43,44). Mutation Q151M does not seem to reduce the HIV-1 replication capacity (45,46).…”
Section: Figmentioning
confidence: 99%